Efecto antibacteriano del aceite esencial de Cocos nucifera frente a Streptococcus mutans (2023)
Cocos nucifera has broad antimicrobial activity, recognized in herbal medicine as a medicine to treat diseases due to its medicinal properties. Streptococcus mutans is a facultative anaerobic microorganism, involved in carious processes. Objective: Determine the antibacterial effect of Cocos nucifera essential oil against S. mutans. Materials and methods: In vitro experimental study. Essential oil was extracted by steam drag, using a Soxhlet system with distilled water as diluent, dilutions from 5% to 100% of the essential oil were made. Reference strain of S. mutans ATCC®25175 seeded on 5% blood agar was used. Sensitivity was evaluated with the agar diffusion method (Kirby-Bauer), with the formation of inhibition zones ≥18 mm. Minimum inhibitory concentration (MIC), minimum bactericidal concentration (MBC) and 50% lethal dose (LD50) were determined, based on the 0.5 turbidity pattern of the McFarland scale, equivalent to 1.5 x 108 UFC/ml. Results: They were obtained by evaluating the degree of sensitivity of S. mutans to concentrations between 5% and 100% of the essential oil of C. nucifera. Concentrations greater than 50% of the essential oil of C. nucifera generated inhibition zones ≥ 18 mm on S. mutans, a MBC of 145.6 mg/dl and an LD50 of 91.0 mg/dl were found. From a 30% dilution, inhibition zones ≥ 15 mm were observed. Conclusion: Cocos nucifera essential oil has an antibacterial effect on S. mutans. Keywords: Streptococcus mutans, Cocos nucifera, minimum inhibitory concentration, minimum bactericidal concentration, lethal dose 50.